2019
DOI: 10.3390/genes10050343
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Multi-Barcoding: DNA Barcoding from Single Ingredient to Complex Mixtures

Abstract: DNA barcoding has been used for decades, although it has mostly been applied to some single-species. Traditional Chinese medicine (TCM), which is mainly used in the form of combination-one type of the multi-species, identification is crucial for clinical usage. Next-generation Sequencing (NGS) has been used to address this authentication issue for the past few years, but conventional NGS technology is hampered in application due to its short sequencing reads and systematic errors. Here, a novel method, Full-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…To verify whether the sleeve peak exists, and to explore the reasons for its appearance, we used NGS and SMRT techniques to perform high-throughput sequencing on highthroughput full-length multiple DNA barcodes based on rDNA with multiple copies of variation [28,32]. Sequencing results confirmed the actual existence of nesting peak; that is, there are different genotypes in the samples, and additional samples have different genotypes and proportions (Figure 3b).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…To verify whether the sleeve peak exists, and to explore the reasons for its appearance, we used NGS and SMRT techniques to perform high-throughput sequencing on highthroughput full-length multiple DNA barcodes based on rDNA with multiple copies of variation [28,32]. Sequencing results confirmed the actual existence of nesting peak; that is, there are different genotypes in the samples, and additional samples have different genotypes and proportions (Figure 3b).…”
Section: Discussionmentioning
confidence: 88%
“…They have furnished novel guidelines and ways for identifying Chinese patent medicines and formulae, which is difficult due to many complex mixtures [27]. Full-length multibarcoding (FLMB) technique of long-read sequencing was proposed to identify biological components in TCM compounds by direct sequencing of ITS2 and psbA-trnH full-length amplicon using SMRT technology [28]. In addition, ribosomes and chloroplasts are abundant organelles in living cells, which means that there are numerous copies of ITS2 and psbA-trnH sequences [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, biological ingredients are also indispensable components for TCM formulas, which could be identified through DNA barcoding-based approach. Out of the plenty of DNA barcodes (Table 1), ITS2, trnL, and psbA-trnH are the most frequently used herbal DNA barcodes, while COI is a wellknown standard DNA barcode for animal materials detection (Coghlan et al, 2012;Li et al, 2018;Zhang et al, 2019a). Numerous studies have also used these representative barcodes to assess the biological ingredients of TCM formulas by detecting their prescribed species using high-throughput sequencing, which has detected 44.4%-100% of the prescribed ingredients of TCM formulas, suggesting the high universality, sensitivity, and specificity of this approach (Cheng et al, 2014;Jia et al, 2017;Joseph and Pe'er, 2021;Li et al, 2018;Xin et al, 2018a;Yao et al, 2022).…”
Section: The Methods For Biological Ingredient Analysismentioning
confidence: 99%
“…Firstly, the inconsistent quality control methods make TCM disputable (Yao Q. et al, 2022). Based on the advancement of sequencing and chromatographic technologies, researchers have combined chemical methods (i.e., HPLC, TLC) (Wolfender et al, 2003;Zhu et al, 2010;Wang Binbin et al, 2021) and biological methods (DNA fragments: ITS2, trnL, trnH-psbA, and COI) (Vences et al, 2005;Jia et al, 2017;Xin et al, 2018a;Xin Tianyi et al, 2018b;Zhang et al, 2019a;Chandrasekara et al, 2021) for quality control of TCM formula through detecting their prescribed ingredients. These initiatives have also yielded significant results in terms of evaluating the quality control of TCM formulas [18][19][20] , which would push forward the digital management of TCM.…”
Section: Figurementioning
confidence: 99%
“…The original idea was that the generation of newborn neurons and neurogenesis occur only during embryonic development and that neuronal death in the adult CNS could only be replaced by the proliferation of glial cells [ 30 ]. NSCs were first isolated from the striatum and hippocampus of adult mice in 1992 [ 31 , 32 ] and are defined as pluripotent cells in the CNS that can self-renew and differentiate into neurons, astrocytes, and oligodendrocytes [ 33 ]. Furthermore, recent extensive studies have shown that adult mammalian pluripotent stem cells in the brain also self-proliferate and differentiate into neurons and glial cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%